2011
DOI: 10.1016/j.jfma.2011.11.008
|View full text |Cite
|
Sign up to set email alerts
|

Occupational hand dermatitis among cement workers in Taiwan

Abstract: We conclude that occupational cement hand dermatitis among cement workers is an important and severe issue in Taiwan, and the most common allergens among cement workers are potassium dichromate, thiuram mix, fragrance mix and cobalt chloride. The high positive rate of chromium hypersensitivity among cement workers reflects the urgency to regulate the addition of ferrous sulfate to cement in Taiwan.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0
4

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(29 citation statements)
references
References 13 publications
(11 reference statements)
0
25
0
4
Order By: Relevance
“…In particular, among construction workers, this prevalence reached 100%. Cobalt chloride, although present in cement in small amounts, was the third most common contact allergen among cconstruction workers with occupational dermatitis, after chromate and epoxy resin . This finding suggests that this concomitant hypersensitivity is not due to a cross‐reaction but to an actual simultaneous sensitization due to combined exposure, given that both of these allergens are present in cement.…”
Section: Discussionmentioning
confidence: 94%
“…In particular, among construction workers, this prevalence reached 100%. Cobalt chloride, although present in cement in small amounts, was the third most common contact allergen among cconstruction workers with occupational dermatitis, after chromate and epoxy resin . This finding suggests that this concomitant hypersensitivity is not due to a cross‐reaction but to an actual simultaneous sensitization due to combined exposure, given that both of these allergens are present in cement.…”
Section: Discussionmentioning
confidence: 94%
“…Cobalt is a potent skin sensitizer and a frequent cause of contact allergy. Studies have shown that the prevalence of contact allergy to cobalt has been high in workers (not patients) in some occupations, including cement workers (7%), dental technicians (12%), and hard metal workers (5%) . The prevalence of cobalt allergy is also higher among dermatitis patients with occupational dermatitis (9.3%) than among those with non‐occupational dermatitis (6.8%), as shown in a study including 11 European countries .…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that the prevalence of contact allergy to cobalt has been high in workers (not patients) in some occupations, including cement workers (7%), dental technicians (12%), and hard metal workers (5%). [1][2][3] The prevalence of cobalt allergy is also higher among dermatitis patients with occupational dermatitis (9.3%) than among those with non-occupational dermatitis (6.8%), as shown in a study including 11 European countries. 4 Sources of exposure to cobalt have not been well studied in general, and it is often suggested that cobalt allergy may be explained by cross-reactivity to nickel or concomitant nickel exposure.…”
Section: Introductionmentioning
confidence: 99%
“…However, fine particulates, <10 μm (PM 10 ) and <2.5 μm (PM 2.5 ), can cause health problems, if one experiences prolonged exposure for 30 to 40 years, because of their respirable nature, and because they may contain potentially harmful concentrates of toxic metals and compounds. Cement dust can cause lung function impairment, pneumoconiosis [5], carcinoma of the lungs and larynx [6,7], and may cause inflammatory changes in the skin, and often leads to skin diseases or autoimmune diseases [8-10]. …”
Section: Introductionmentioning
confidence: 99%